THE EFFECT OF BIOGRAPHICAL CHARACTERISTICS, LEVEL OF MOTIVATION AND LEVEL OF ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL CITIZENSHIP BEHAVIOR AS INTERVENING VARIABLE AT PT. GARUDA INDONESIA - Izza, Sayyidatul; Djuardi, Dian Komarsyah (Jurnal Kompetitif Bisnis, 2022)
This study aims to determine the effect of biographical characteristics, level of motivation and level of organizational commitment on employee performance with organizational citizenship behavior as an intervention. This research method uses explanatory research techniques with a quantitative approach with the object of research at PT. Garuda Indonesia. Collecting data using a questionnaire with a sample of 65 respondents, analyzed using Smart PLS. This study concludes that organizational commitment affects employee performance, organizational motivation affects organizational citizenship behavior, organizational commitment affects organizational citizenship behavior, organizational citizenship behavior affects employee performance, organizational citizenship behavior variable mediate the influence of motivation on performance and organizational citizenship behavior variable mediate the effect of organizational commitment on employee performance.